To Put It Differently: A Cross-Disciplinary Investigation of Reformulation Markers in Student Essays. Issue 9 (21st October 2021) - Barabadi, Elyas; Golparvar, Seyyed Ehsan; Arghavan, Amanollah
ABSTRACT: This study examined the forms and functions of reformulation markers (RMs) in the three disciplines of philosophy, economics, and biology to see whether there is any disciplinary variation regarding these linguistic devices and their functions in essays written by undergraduate students. To this purpose, two corpora of university students' essays were prepared using Michigan Corpus of Upper-level Student Essays and Sketch Engine. The functions of RMs were examined based on an established framework. Moreover, two further functions, clarification and exemplification, also emerged out of the data. The findings of this corpus-based study revealed that essays written in economics contained the highest frequency of RMs. As for the functions, the macro-function related to the interpretation of explicit meaning was the most common in all three disciplines. The baseline comparison revealed that reformulation is used almost similarly by the students for whom English is a native language and those for whom English is a second language: however, some remarkable differences existed with the way first-year students use RMs.